Comparing the Structure and Robustness of Passifloraceae - Floral Visitor and True Pollinator Networks in a Lowland Atlantic Forest - Cristine Rodrigues Benevides; Darren M Evans; Maria Cristina Gaglianone (Sociobiology)
We investigated the plant-pollinator interactions of Passifloraceae occurring in fragments of lowland semi-deciduous Atlantic forest. We described floral biology, pollination syndromes and the pollinators of Passiflora alata, Passiflora kermesina, Passiflora suberosa, Passiflora malacophylla and Mitostemma glaziovii. We examined the robustness of the interaction networks to species loss, a plausible scenario resulting from forest fragmentation. The effects of pollination syndrome (flower size) on network robustness was also examined. Passiflora alata, P. malacophylla and P. suberosa were pollinated by bees of different corporal sizes. P. kermesina and M. glaziovii presented the highest diversity of visitors and were pollinated mainly by hummingbirds and butterflies, respectively. Through the analysis of the networks we differentiate the structures of the flower-visitor network with the ‘true’ plant-pollinator network. The robustness of the flower-visitor network to animal loss was generally high, but it declined when only true pollinators were included in the network. The sequential loss of plants from the flower-visitor network resulted in low robustness: the loss of key plants could have significant cascading effects on the animals feeding on them within the forest fragment. Future studies should consider the interactions between all flowering plants and animals in this habitat in order to guide conservation and management plans for these forest fragments.